Clinical Application of Targeted Deep Sequencing in Solid‐Cancer Patients and Utility for Biomarker‐Selected Clinical Trials. (12th July 2017) - Kim, Seung Tae; Kim, Kyoung‐Mee; Kim, Nayoung K.D.; Park, Joon Oh; Ahn, Soomin; Yun, Jae‐Won; Kim, Kyu‐Tae; Park, Se Hoon; Park, Peter J.; Kim, Hee Cheol; Sohn, Tae Sung; Choi, Dong Il; et al.
Abstract : Abstract: Molecular profiling of actionable mutations in refractory cancer patients has the potential to enable "precision medicine, " wherein individualized therapies are guided based on genomic profiling. The molecular‐screening program was intended to route participants to different candidate drugs in trials based on clinical‐sequencing reports. In this screening program, we used a custom target‐enrichment panel consisting of cancer‐related genes to interrogate single‐nucleotide variants, insertions and deletions, copy number variants, and a subset of gene fusions. From August 2014 through April 2015, 654 patients consented to participate in the program at Samsung Medical Center. Of these patients, 588 passed the quality control process for the 381‐gene cancer‐panel test, and 418 patients were included in the final analysis as being eligible for any anticancer treatment (127 gastric cancer, 122 colorectal cancer, 62 pancreatic/biliary tract cancer, 67 sarcoma/other cancer, and 40 genitourinary cancer patients). Of the 418 patients, 55 (12%) harbored a biomarker that guided them to a biomarker‐selected clinical trial, and 184 (44%) patients harbored at least one genomic alteration that was potentially targetable. This study demonstrated that the panel‐based sequencing program resulted in an increased rate of trial enrollment of metastatic cancer patients into biomarker‐selected clinical trials. Given the expanding list of biomarker‐selected trials, the guidance percentage to matched trials is anticipated to increase. Abstract : Advances in sequencing technologies and improved algorithms for detecting specific molecular aberrations make it possible to perform biomarker‐driven clinical trials. The analytical sensitivity and clinical validity have not yet been demonstrated in a large cohort. This article describes the implementation of a targeted‐sequencing panel in a precision oncology clinic and the feasibility of a clinic‐based molecular screening program.